Effects of spray drying conditions of microencapsulation of Amaranthus gangeticus extract on drying behaviour - Chong, Pik Han; Yusof, Yus Aniza; Aziz, Mohammad Gulzarul; Naim, Mohd Nazli; Chin, Nyuk Ling; Syed Muhammad, Sharifah Kharidah (Elsevier, 2014)
The aim of the study is to investigate the drying behaviour of spray-dried betacyanin pigment powder extracted from Amaranthus gangeticus as influenced by spray drying conditions which include inlet temperature, feed concentration and feed flow rate. β-cyclodextrin and maltodextrin were used as encapsulating agents. Central composite design was applied to model spray drying process with seventeen and thirteen formulations were conducted, respectively. Several parameters including feed moisture, powder moisture, drying ratio, productivity, surface tension, density and viscosity of feed were determined experimentally. The drying rate, droplet size and drying time of A. gangeticus extracted betacyanins were investigated during spray drying.